Elaboration of new method of enzyme adsorption on silicalite and nano beta zeolite for amperometric biosensor creation - Soldatkin, O.O.; Ozansoy Kasap, B.; Akata Kurc, B.; Soldatkin, A.P.; Dzyadevych, S.V.; El’skaya, A.V. (Вiopolymers and Cell, 2014)
Aim. Optimization of a new method of enzyme immobilization for amperometric biosensor creation. Methods. The amperometric biosensor with glucose oxidase immobilized on zeolites as bioselective elements and platinum disk electrode as transducers of biochemical signal into the electric one was used in the work. Results. The biosensors based on glucose oxidase adsorbed on zeolites were characterized by a higher sensitivity to glucose and a better inter-reproducibility. The best analytical characteristics were obtained for the biosensors based on nano beta zeolite. It has been found that an increase in the amount of zeolite on the surface of amperometric transducer may change such biosensor parameters as sensitivity to the substrate and duration of the analysis. Conclusions. The proposed method of enzyme immobilization by adsorption on zeolites is shown to be quite promising in the development of amperometric biosensors and therefore should be further investigated. Мета. Оптимізація нового методу іммобілізації ферментів для розробки амперометричних біосенсорів. Методи. Використано іммобілізовану глюкозооксидазу на цеоліті як біоселективний елемент біосенсора та платиновий дисковий електрод – як амперометричний перетворювач біохімічного сигналу в електричний. Результати. Біосенсор на основі глюкозооксидази, адсорбованої на цеолітах, вирізняється високою чутливістю до глюкози та покращеною інтер-відновлюваністю виготовлення біосенсорів. Найкращі аналітичні характеристики притаманні біосенсору на основі нано-бета цеоліту. Встановлено, що при зміні кількості цеолітів на поверхні амперметричного перетворювача можна варіювати параметри біосенсора, такі як чутливість до субстрату та час аналізу. Висновки. Показано, що запропонований метод іммобілізації, а саме – адсорбція ферментів на цеолітах є дуже перспективним при розробці амперометричних біосенсорів. Цель. Оптимизация нового метода иммобилизации ферментов для разработки амперометрических биосенсоров. Методы. Использовали иммобилизованную глюкозооксидазу на цеолитах как биоселективный элемент биосенсора и платиновый дисковый электрод – как амперометрический преобразователь биохимического сигнала в электрический. Результаты. Биосенсор на основе глюкозооксидазы, адсорбированной на цеолитах, отличается высокой чувствительностью к глюкозе и улучшенной интер-воспроизводимостью приготовления биосенсоров. Наилучшими аналитическими характеристиками обладает биосенсор на основе нано-бета цеолита. Установлено, что при изменении количества цеолитов на поверхности амперометрического преобразователя можно менять параметры биосенсора, такие как чувствительность к субстрату и время анализа. Выводы. Показано, что предложенный метод иммобилизации, а именно – адсорбция ферментов на цеолитах является перспективным при разработке амперометрических биосенсоров.